1994
DOI: 10.3109/01913129409016279
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Light Chains and the Kidney: An Overview

Abstract: Monoclonal immunoglobulins and free immunoglobulin light chains are produced by plasma cells as a result of their clonal expansion in plasma cell dyscrasia. These proteins are pivotal in the development of pathologic and clinical symptoms of plasma cell dyscrasia and renal manifestations are frequently the presenting and leading features of this process. The spectrum of pathology associated with monoclonal light chains includes light-chain cast nephropathy and tissue deposits derived from the monoclonal light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is worth mentioning that kidney injury from other cationic macromolecules has been reported in the literature. Cationic light chains have been shown to cause tubular and glomerular injury independent of cast formation17 in patients with multiple myeloma and B-cell lymphoproliferative disorders. Experimental evidence also suggests direct tubular injury by meglumine, a small cationic molecule commonly used in intravenous contrast agents 18.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that kidney injury from other cationic macromolecules has been reported in the literature. Cationic light chains have been shown to cause tubular and glomerular injury independent of cast formation17 in patients with multiple myeloma and B-cell lymphoproliferative disorders. Experimental evidence also suggests direct tubular injury by meglumine, a small cationic molecule commonly used in intravenous contrast agents 18.…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical reports regarded FLC as biomarkers of many inflammatory diseases, such as autoimmune disease, diabetes mellitus and CNS inflammation 42, 43 . Furthermore, elevated FLC depositing in the extracellular matrix often resulted in inflammation and tissue injury; two examples of this phenomenon include amyloid light chain amyloidosis (AL-AM) and light chain deposition disease (LCDD) 4446 . Recently, it was found that FLC might be involved in the induction of hypersensitivity reaction by activating mast cells and promoting their degranulation via unknown receptors 47, 48 .…”
Section: Introductionmentioning
confidence: 99%